Prinsip Perlindungan Hukum Pekerja atas Pengurangan Upah di Masa Pandemi Covid 19 - Dika, Mega Surya Mahar; Harianto, Aries (Department of Constitutional Law, Faculty of Law, University of Jember, Indonesia, 2021)
Pandemi COVID 19 mengakibatkan sebagian besar Pengusaha dipaksa untuk menghentikan atau mengurangi kegiatan usahanya. Ini berarti akan terjadi Pemutusan Hubungan Kerja atau pengurangan para pekerjanya. Hal ini juga memaksa pekerja untuk Work From Home (WFH) atau tidak bekerja sama sekali. Ini berarti berkurangnya atau terhentinya sumber nafkah pekerja dan keluarganya. Akibat Pandemi COVID 19, bagi Pemerintah Pemutusan Hubungan Kerja adalah bertambahnya jumlah pengangguran yang dapat menimbulkan keresahan social. Ini berarti berkurangnya atau terhentinya sumber nafkah pekerja dan keluarganya. Akibat Pandemi COVID 19, bagi Pemerintah Pemutusan Hubungan Kerja adalah bertambahnya jumlah pengangguran yang dapat menimbulkan keresahan sosial.Kata Kunci: Perlindungan Hukum, Pengurangan Upah, Pandemi Covid 19.The COVID-19 pandemic has resulted in most entrepreneurs being forced to stop or reduce their business activities. This means that there will be Termination of Employment or reduction of its workers. It also forces workers to work from home (WFH) or not work at all. This means reduced or stopped sources of livelihood for workers and their families. As a result of the COVID-19 Pandemic, for the Government, termination of employment is an increase in the number of unemployed which can cause social unrest. This means reduced or stopped sources of livelihood for workers and their families. As a result of the COVID-19 Pandemic, for the Government, termination of employment is an increase in the number of unemployed which can cause social unrest.Keywords: Legal Protection, Wage Reduction, Pandemic Covid 19.